Educational research : contemporary issues and practical approaches - Wellington, Jerry (Continuum, 2004)
This guide answers questions such as: What is educational research?; What research has been done before?; How should research be conducted? There is also advice on interviewing, case studies, surveys, documentary research, the Delphi method and the use of focus groups.